Reconstruction of Vocational-Based Mathematics Teaching Materials using a Smartphone - Sumandya, I Wayan; Widana, I Wayan (Universitas Pendidikan Ganesha, 2022)
Mathematics is one of the essential subjects for vocational students because it is very dominant in developing science and technology. This study aims to produce vocational-based mathematics teaching materials using smartphones that meet the valid, practical, and effective prerequisites. The progressing model used in the test is ADDIE. The validity of the featured material was surveyed by three materials specialists and three media specialists using an assessment and analyzed using the Gregory arrangement. The results of the assessment obtained that the material displayed meets practical needs. The ease of use perspective was assessed by giving a poll to research researchers using the Client Experience Survey (UEQ) and a survey to students using the Framework Convenience Scale (SUS) test. The assessment results based on the Client Experience Poll (UEQ) obtained a normal value of 89.56 with a good standard. As a consequence of the Ease of Use Framework assessment, it was found that normal 89.44 was recognized and within the range of generally very good. The effectiveness of teaching materials is assessed to provide a trial of learning outcomes to students and dissected based on traditional culmination values. Traditional fulfillment awards earned 95%. The advantages of the teaching materials are photos, test questions, and conversational materials according to practice for vocational students, which students can use for independent and group study, both within and outside the organization. Given these results, it can be very well concluded that the vocational-based mathematics learning materials using smartphones have fulfilled the valid, practical, and effective components to be utilized during learning.